Linking myofilaments to sudden cardiac death: recent advances. (16th March 2017) - Huke, Sabine
Abstract : This focused review explores recent advances in understanding how mutations in myofilament proteins promote arrhythmias and sudden cardiac death. Abstract: The major goal of this focused review is to highlight some of the recent advances and remaining open questions about how a mutation in a myofilament protein leads to an increased risk for sudden cardiac death (SCD). The link between myofilaments and SCD has been known for over 25 years, but identifying mutation carriers at risk for SCD is still a challenge and currently the only effective prevention is implantation of a defibrillator (ICD). In addition to recognized risk factors, other contributing factors need to be considered and assessed, e.g. 'microvascular dysfunction', to calibrate individual risk more accurately. Similarly, improving our understanding about the underlying mechanisms of SCD in patients with sarcomeric mutations will also allow us to design new and less invasive treatment options that will minimize risk and hopefully make implantation of an ICD unnecessary.